The Itinerant Curriculum as a Key to Responsiveness in the Era of the Fourth Industrial Revolution in Nigerian Higher Education - Fomunyam, Kehdinga George (International Journal of Learning, Teaching and Educational Research, 2022)
The current age of the Fourth Industrial Revolution (4IR) brings together digital, physical, and biological awareness in ways never before seen. The transition has contributed to new technology and developments, such as robotics, the Internet of Things, augmented reality, and artificial intelligence. As a nation, Nigeria is still behind with preparations for its future through appropriate, unique educational practices in this era for its citizens. This is because the quality of Nigeria’s higher education curriculum has not improved much. To boost the responsiveness of Nigeria’s curriculum in this technological era, this theoretical paper explores the itinerant curriculum as an alternative direction to other highlighted alternatives in the literature. The paper explains how the itinerant curriculum can be used to achieve economic, cultural, disciplinary, and learning responsiveness in the era of the 4IR. The paper concludes that the itinerant curriculum is an important tool that can help Nigerian higher education achieve curriculum responsiveness. https://doi.org/10.26803/ijlter.21.7.21